Birth weight and blood lipid levels in Spanish adolescents: Influence of selected APOE, APOC3 and PPARgamma2 gene polymorphisms. The AVENA Study - Fuentes Miguel; Nova Esther; Martí Amelia; González-Lamuño Domingo; Moreno Luis A; Ortega Francisco B; Labayen Idoia; Ruiz Jonatan R; Redondo-Figuero Carlos; Martínez J Alfredo; Sjöström Michael; Castillo Manuel J (BMC, 2008)
Abstract Background There is increasing evidence indicating that genes involved in certain metabolic processes of cardiovascular diseases may be of particular influence in people with low body weight at birth. We examined whether the apolipoprotein (APO) E, APOC3 and the peroxisome proliferator-activated receptor-γ-2 (PPARγ2) polymorphisms influence the association between low birth weight and blood lipid levels in healthy adolescents aged 13-18.5 years. Methods A cross-sectional study of 502 Spanish adolescents born at term was conducted. Total (TC) and high density lipoprotein cholesterol (HDLc), triglycerides (TG), apolipoprotein (apo) A and B, and lipoprotein(a) [Lp(a)] were measured. Low density lipoprotein cholesterol (LDLc), TC-HDLc, TC/HDLc and apoB/apoA were calculated. Results Low birth weight was associated with higher levels of TC, LDLc, apoB, Lp(a), TC-HDLc, TC/HDLc and apoB/apoA in males with the APOE ε3ε4 genotype, whereas in females, it was associated with lower HDLc and higher TG levels. In males with the APOC3 S1/S2 genotype, low birth weight was associated with lower apoA and higher Lp(a), yet this association was not observed in females. There were no associations between low birth weight and blood lipids in any of the PPARγ2 genotypes. Conclusion The results indicate that low birth weight has a deleterious influence on lipid profile particularly in adolescents with the APOE ε3/ε4 genotype. These findings suggest that intrauterine environment interact with the genetic background affecting the lipid profile in later life.